Performance Analysis of Bank BNI Syariah Before and After Becoming Bank Syariah Indonesia (BSI): English - Nasrifah, Maula (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam Syarifuddin Lumajang, 2023)
The government's policy of merging three state-owned sharia banking companies provides market share opportunities for Bank Syariah Indonesia to support the growth of sharia banking. The three banks are Bank Syariah Mandiri (BSM), Bank Rakyat Indonesia (BRIS), and Bank Negara Indonesia Syariah (BNIS). The aim of this research is to describe the performance of Bank BNI Syariah before and after becoming Bank Syariah Indonesia using the filed research method with interview data which is then analyzed. The research results show that Islamic banks are experiencing very rapid development, so they require special strategies to become superior, one of which is by improving the banking service system and continuously making improvements. In the process, there have been several changes in the performance system of sharia banks, including increasing the types of financing and types of savings currently available at Indonesian sharia banks. Like pension savings which only came into existence when it was merged into Bank Syariah Indonesia and this was followed by other similar product